Pembelajaran Matematika Realistik untuk meningkatkan Hasil Belajar Matematika Siswa - Fenny Anggreni; Mariani . (At-Tarbawi : Jurnal Pendidikan, Sosial dan Kebudayaan, 2020)
Realistic mathematics learning is a teaching approach that starts from "real" things for students. Fraction problems are often found in daily life and are felt difficult by most students in SD.N.Kp.Baroh Langsa so that student learning outcomes are still relatively low. The purpose of this research is to find out whether the use of Realistic Mathematics Learning can improve the learning outcomes of fourth-grade students of Semester II SD.N.Kp.Baroh Langsa. The approach used in this study is a qualitative approach and the type of research is classroom action research consisting of 2 cycles. The research subjects are grade IV students of SD.N.Kp.Baroh Langsa, amounting to 33 students. Data analysis used a comparative descriptive analysis technique by comparing conditions in cycle I and cycle II. Based on the results of research at the end of the second cycle it is known that there has been an increase in the class average of 29.16% from an average ofthe first cycle test of only 58.18 up to 75.15. Then completeness of student learning also increased by 87.50% from the first cycle that has been completed only 16 students to 30 students. So that most of the fourth-grade students of SD.N.Kp.Baroh Langsa experienced an increase in learning outcomes in fractional material. Thus it can be concluded that the use of realistic mathematics learning in fraction material can improve the learning outcomes of fourth-grade students of the second semester of SD.N.Kp.Baroh Langsa.